Pemanfaatan Electronic Word of Mouth pada Masa Pandemi Covid-19 oleh UMKM (Studi Kasus Salad Mantoel) - Aldi Nirjana; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The impact of coronavirus or Covid-19 seems to have an impact on all sectors, especially tourism and other sectors. The World Bank projects indonesia's economic growth this year will be depressed at 2.1 percent. In the midst of the pandemic there are various opportunities for business people, especially MSMEs who with small capital can start a business by utilizing Electronic Word Of Mouth on social media. This research is expected to be a reference for newly established MSMEs and use Electronic Word Of Mouth as a means of promotion. This method of research uses qualitative research methods with data collection in the form of interviews, observations, and documentation. The subject in this study was MSMEs Salad Mantoel, The object of this study was the utilization of Electronic Word Of Mouth on MSMEs Salad Mantoel. The interview was conducted to 5 respondents, in this case the researchers did documentation of the sales results, and testimonials from buyers from MSMEs Salad Mantoel. Based on data obtained by researchers from interviews with respondents and other evidence in the form of testimonial documentation. For almost 2 years running, Mantoel Salad still has not maximized promotion using Electronic Word Of Mouth on social media, Mantoel Salad only promotes products using Whatsapp and Facebook media. So the products of Mantoel Salad still cannot be widely known by the public.Dampak Virus Corona atau Covid-19 nampaknya berimbas pada semua sektor terutama pariwisata dan sektor-sektor lainnya. Bank Dunia memproyeksikan pertumbuhan ekonomi Indonesia di tahun ini akan tertekan di level 2,1 persen. Ditengah pandemi muncul berbagai macam peluang untuk pelaku bisnis, terutama UMKM yang dengan modal kecil dapat memulai usaha dengan memanfaatkan Electronic Word Of Mouth pada media sosial. Penelitian ini diharapkan dapat menjadi acuan untuk UMKM yang baru berdiri dan menggunakan Electronic Word Of Mouth sebagai sarana promosi. Metode pada penelitian ini menggunakan metode penelitian kualitatif dengan pengumpulan data berupa wawancara, observasi, dan dokumentasi. Subjek dalam penelitian ini adalah UMKM Salad Mantoel, Objek dari penelitian ini adalah pemanfaatan Electronic Word Of Mouth pada UMKM Salad Mantoel. Wawancara dilakukan kepada 5 responden, dalam hal ini peneliti melakukan dokumentasi dari hasil penjualan, dan testimoni dari pembeli dari UMKM Salad Mantoel. Berdasarkan data yang diperoleh peneliti dari wawancara kepada responden serta bukti – bukti lain berupa dokumentasi testimoni. Selama hampir 2 tahun berjalan, Salad Mantoel masih belum memaksimalkan promosi menggunakan Electronic Word Of Mouth pada media sosial, Salad Mantoel hanya melakukan promosi produk menggunakan media Whatsapp dan Facebook. Sehingga produk dari Salad Mantoel masih belum bisa dikenal luas oleh masyarakat.